CMTM8 variants influence BNT162b2 COVID-19 vaccination response by regulating granulocytic/polymorphonuclear myeloid-derived suppressor cell activity - Testori, Alessandro; Mulas, Antonella; Marongiu, Mara; Orrù, Valeria; Lobina, Monia; Piras, Maria Grazia; Lutzu, Erika; Curreli, Nicolò; Politi, Cristina; Mobrici, Marco; Iervasi, Giorgio; Corda, Daniela; et al. (Frontiers in Immunology, 2026)
BackgroundThe immunoglobulin level following vaccination against SARS-CoV-2 results from a multifaceted immunological process involving cells and molecules that determine its efficacy and protect us against severe infection outcomes. The observed heterogeneity in the immune response to vaccination is partly attributable to host genetic factors; however, this genetic contribution has only been partially explored.MethodsTo elucidate the mechanisms underlying the antibody response elicited by the Pfizer-BioNTech vaccine, we conducted a genome-wide association study on anti-spike immunoglobulin G levels measured in 1,968 Italian individuals who received two doses of the vaccine, selected from a larger cohort of 7,169 volunteers characterized for 8 million genetic variants. Sex, age, body mass index, smoking habit, and time elapsed between vaccine administration and blood draw were accounted as covariates in the linear regression model.ResultsWe identified a novel signal of association on chromosome 3 in the intronic region of the CMTM8 gene and confirmed one previously identified at the HLA locus close to the HLA-B gene. The lead SNP in the CMTM8 gene, rs7643677 (p-value = 2.095×10-8), is associated with anti-S IgG levels and with the expression level of CD66b on granulocytic/polymorphonuclear myeloid-derived suppressor cells.ConclusionsThese findings support a role for CMTM8 in regulating the suppressive activity of specific immune cells, and suggest a potential interplay among genetic, humoral, and cellular mechanisms underlying the immune response to SARS-CoV-2 vaccination.